Prokrastinasi akademik pada mahasiswa yang aktif berorganisasi: Bagaimana peranan regulasi diri dan efikasi diri? - yubilea, martha novena; Herlan Pratikto; Suhadianto (INNER: Journal of Psychological Research, 2023)
Abstract This research aims to determine the relationship between self-regulation, self-efficacy, and academic procrastination in students who are active in organizations. The research participants totaled 210 students who were recruited using convenience sampling techniques. The instruments in this research used the academic procrastination scale, self-regulation scale, and self-efficacy scale. Through psychometric testing, all instruments have good item discrimination and reliability indices. Not all assumption tests can be met so the data analysis technique in this research uses Bayesian Regression. The results of hypothesis testing show that there is a significant simultaneous correlation between self-regulation, self-efficacy and academic procrastination in students who are active in organizations. Implications for further research are discussed. Keywords: Academic procrastination; Bayesian method, Self-Efficacy; Self-regulation; Student Organization.